Strategy for Implementing Reliability Centered Maintenance to Improve Productivity in the Cajuput Oil Production Process at PT. Eagle Indo Pharma (International Journal of Economics and Management Research, 2026)
One of the objectives of this study is to identify and analyze problems that have an impact on increasing productivity in cajuput oil production. The method used Reliability Centered Maintenance (RCM) is used to determine the most effective maintenance approach based on system reliability, using the Failure Mode and Effects Analysis (FMEA), Fault Tree Analysis (FTA), and Logic Tree Analysis (LTA) approaches in order to overcome ambiguity and uncertainty in risk assessment. The results of the study using the Failure Mode and Effect Analysis (FMEA) method, there are failures that are a priority for improvement based on the risk priority number (RPN) value. The highest RPN values ​​are Labeling Machines, Filling Machines, Capping Machines with RPN values ​​of 294, 288 and 252 in the high criticality category. The maintenance carried out is routine checks after and before using the tool or machine, carrying out Checks and maintenance according to the Cleaning, Inspection, Lubrication, Tighting (CILT) checksheet. The downtime rate from July to August 2024 decreased by 4.72%, previously the weekly downtime rate was 19.09% after 2 weeks the downtime rate dropped to 14.37%. Shows that the selection of the maintenance model has been successful in increasing the reliability, efficiency and overall performance of the system.